Development of an informative web application for the promotion of ecotourism: A case study - Seijas-Díaz, José; Martell, Karla; Casas, Roi; Schrader, Juan; Cueto-Orbe, Rosa; Rengifo-Amasifen , Roger; Barbachán-Ruales, Enrique; Torres-Silva, Cinthya (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: En a global context where technology is essential for the search of information and decision-making by tourists, the creation of digital platforms is a key strategy to promote sustainable tourism practices.OBJECTIVES: We aim to develop an informative web application aimed at promoting ecotourism in Lake Cuipari, using it as a case study.METHODS: The software development followed the phases established in the Agile methodology Extreme Programming: i) Exploration, ii) Planning, iii) Interactions, iv) Production, and v) Maintenance. To ensure the quality of the software product, we applied black-box testing.RESULTS: We successfully developed a functional informational web application with two panels, administrative and visitor. The web application allows users to learn about the location of Lake Cuipari, explains access conditions, and provides information about native species in and around the lake. These species are categorized into birds, amphibians, and fish, with academic, scientific, and tourist interest.CONCLUSION: The informational web application serves as a digital platform that enables the municipality and the local community to promote ecotourism in Lake Cuipari for the sake of its preservation and sustainability. This is achieved through the increased provision of information for potential tourists.